Comparative analysis of the effect of IV administered acid suppressants on gastric pH in dogs. (5th February 2020) - Kuhl, Amanda; Odunayo, Adesola; Price, Josh; Hecht, Silke; Marshall, Kristen; Steiner, Joerg; Tolbert, M. Katherine
Abstract: Background: Upper gastrointestinal (GI) ulceration and bleeding in critically ill dogs can cause severe anemia and increase morbidity. Acid suppressants using proton pump inhibitors or histamine‐2 receptor blockers administered IV is commonly recommended. Hypothesis/Objectives: To evaluate the efficacy of IV administered esomeprazole, pantoprazole, and famotidine constant rate infusion (CRI) on increasing the intragastric pH of dogs. We hypothesized that esomeprazole and famotidine CRI would provide superior acid suppression compared to pantoprazole and reach pH goals for the treatment of GI bleeding. Animals: Nine healthy research Beagles. Methods: Randomized, 3‐way crossover. Dogs received pantoprazole or esomeprazole at 1 mg/kg IV q12h and famotidine with a loading dose of 1 mg/kg followed by 8 mg/kg IV CRI daily for 3 consecutive days. The intragastric pH was recorded at baseline and for 72 hours of treatment. The mean pH and the mean percentage time (MPT) the intragastric pH was ≥3 or ≥4 were compared among and within treatment groups. Results: Significant increases in mean pH ( P  < 0.0001), MPT ≥3 ( P  < 0.001), and MPT ≥4 ( P = 0.0006) were noted over time with all 3 treatments. The time effect did not differ by treatment for mean pH, MPT ≥3, and MPT ≥4 ( P = .29, .56, and .37, respectively); however, only esomeprazole and famotidine CRI achieved the goals established for the treatment of gastroduodenal ulceration in people. Conclusions and Clinical Importance: Famotidine CRI and esomeprazole might be superior acid suppressants compared to standard doses of pantoprazole for the first 72 hours of treatment.